Magnetic composite adsorbent for removing tetracycline and malachite green as well as preparation method and application of magnetic composite adsorbent
The magnetic composite adsorbent composed of mafferite and iron tetraoxide was prepared by the sol-gel one-pot method, which solved the problem of efficient removal of tetracycline and malachite green in water and the recovery of adsorbents, and achieved efficient, environmentally friendly and economical wastewater purification effect.
Patent Information
- Application Number
- CN202510140780.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to efficiently remove tetracycline and malachite green from water, especially at high concentrations, and adsorbents are difficult to quickly separate and reuse.
The sol gel one-pot method is used to prepare magnetic composite adsorbent, whose main components are mafite and iron tetraoxide. The adsorbent is prepared by controlling a low calcining temperature (350-445℃), which has high adsorption capacity and magnetism, which is easy to recover.
It has achieved efficient removal of tetracycline and malachite green, with a high removal rate, a fast removal rate, a short removal time, and the adsorbent can be quickly recovered by magnetic force and reused multiple times, which has the advantages of environmental protection and energy saving.
Smart Images

Figure CN119771378A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of adsorption technology, and in particular to a magnetic composite adsorbent for removing tetracycline and malachite green, and a preparation method and application thereof. Background Art
[0002] Malachite green (MG) is a triphenylmethane organic compound. It is widely used in textile and leather dyeing, aquaculture and other industries because of its low price, easy coloring and good bactericidal effect. However, malachite green has strong biological toxicity and will reduce the light transmittance of water bodies, weaken the photosynthesis of aquatic plants, lead to a decrease in the oxygen content of water bodies, and inhibit the activity of aquatic organisms. Tetracycline (TC) is widely regarded as an effective antibiotic. It plays an important role in many fields such as pharmaceuticals, aquaculture, and agriculture. However, tetracycline has the characteristics of low absorption efficiency and slow metabolism, which leads to its large-scale discharge into the environment through the excretion system, causing problems such as enhanced resistance of pathogens and resistance gene transfer. Therefore, the degradation and treatment of dye wastewater and antibiotics in water are imminent.
[0003] At present, in view of the complex water quality, difficult biodegradation and rich in organic matter, physical treatment, chemical treatment, biological treatment and other combined processes are mainly used to treat wastewater. Among them, the most widely used are photocatalysis and adsorption. The photocatalysis method uses light energy to excite electrons on the surface of the catalyst to produce active oxidants (such as hydroxyl radicals, superoxide radicals, etc.), thereby oxidizing and degrading organic matter in organic wastewater. The photocatalysis method has the advantages of high treatment efficiency and the ability to destroy the molecular structure of dyes, but its treatment effect is often affected by factors such as light conditions, catalyst types and stability. In addition, the photocatalysis method may face problems such as catalyst deactivation and decreased treatment efficiency when treating high-concentration dye wastewater, and can only treat dye wastewater with lower concentrations. The adsorption method is suitable for treating wastewater of various concentrations and types, has strong adaptability, and can be carried out without light conditions.
[0004] Adsorption is one of the physical methods commonly used in wastewater treatment. Its principle is to use adsorbents to adsorb organic dyes, antibiotics and other pollutants in wastewater, so that they are transferred from water to the surface of the adsorbent, thereby purifying the wastewater. During the adsorption process, adsorption occurs between pollutant molecules and the surface of the adsorbent, which is mainly affected by van der Waals forces, electrostatic effects, hydrogen bonds and other forces. Through adsorption, pollutants are transferred from water to the surface of the adsorbent, thereby purifying the wastewater. The most commonly used adsorbents in industry are activated carbon, molecular sieves, iron oxide, aluminum oxide, silica gel, activated alumina, polymer resins, etc. Different adsorbents have different adsorption characteristics and effects. The adsorption method has become one of the treatment methods with broad prospects because of its low cost, simple operation, high applicability, environmental friendliness, reusability, high treatment efficiency and non-toxic by-products. In addition, in the adsorption material, since magnetism makes the material easy to separate, the application prospects of magnetic composite materials are even broader.
[0005] However, the adsorption method only transfers the dye in the treated wastewater, and it must be regenerated or destroyed later, otherwise it is easy to cause secondary pollution. Therefore, magnetic composite adsorbents have become a major research hotspot. Composite adsorbents are usually composed of a variety of materials with adsorption properties. The materials can produce synergistic effects, thereby enhancing the adsorption effect, which has greater advantages in treating high-concentration, difficult-to-degrade dye wastewater. In addition, composite adsorbents usually have a larger specific surface area and an appropriate pore size distribution, which significantly improves the sedimentation performance of composite adsorbents in wastewater.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first purpose of the present invention is to provide a method for preparing a magnetic composite adsorbent for removing tetracycline and malachite green, using water as a solvent and controlling a relatively low calcination temperature. The main components of the magnetic composite adsorbent prepared by the method include magnesium ferrite and ferrosoferric oxide, and the magnetic composite adsorbent has a good treatment effect on tetracycline and malachite green, with a high removal rate, a fast removal rate and a short removal time.
[0008] The second object of the present invention is to provide a magnetic composite adsorbent for removing tetracycline and malachite green, the main components of which are magnesium ferrite and ferrosoferric oxide.
[0009] The third object of the present invention is to provide the use of a magnetic composite adsorbent in the adsorption and removal of tetracycline and malachite green.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] The present invention first provides a preparation method of a magnetic composite adsorbent for removing tetracycline and malachite green, comprising the following steps: mixing a magnesium source, an iron source, citric acid and water and performing a complex reaction to obtain a sol; adjusting the pH of the sol and heating to form a gel; igniting the gel to obtain a precursor; calcining the precursor to obtain the magnetic composite adsorbent; wherein the calcination temperature is less than 450°C; and main components of the magnetic composite adsorbent include magnesium ferrite and ferrosoferric oxide.
[0012] Furthermore, the calcination temperature is 350-445°C.
[0013] Furthermore, during the mixing process, the molar ratio of the magnesium element in the magnesium source to the iron element in the iron source is 0.8-1.2:2.
[0014] Furthermore, the ratio of the molar amount of the citric acid to the sum of the molar amounts of the magnesium element in the magnesium source and the iron element in the iron source is 0.8-1.2:1.
[0015] Furthermore, the temperature of the complexation reaction is 40-90°C.
[0016] Furthermore, the pH of the sol is adjusted to 7-11.
[0017] The present invention further provides a magnetic composite adsorbent prepared by the preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green, wherein the magnetic composite adsorbent is composed of magnesium ferrite and ferrosoferric oxide.
[0018] The invention also provides application of the magnetic composite adsorbent in adsorbing and removing tetracycline and malachite green.
[0019] Furthermore, the removal rate of the magnetic composite adsorbent for a tetracycline solution with a concentration of ≤10 mg / L is ≥65%.
[0020] Furthermore, the removal rate of the magnetic composite adsorbent for malachite green solution with a concentration of ≤300 mg / L is ≥90%.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green provided by the present invention uses water as a solvent and controls a relatively low calcination temperature. The main components of the magnetic composite adsorbent prepared by the method include magnesium ferrite and ferrosoferric oxide. The magnetic composite adsorbent has a good treatment effect on tetracycline and malachite green, with a high removal rate, a fast removal rate, and a short removal time.
[0023] (2) The magnetic composite adsorbent prepared by the preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green provided by the present invention still has a good removal effect on malachite green with a higher concentration.
[0024] (3) The preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green provided by the present invention adopts a sol-gel one-pot process, which is simple and convenient to operate, takes a short time, and has low price of magnesium and a wide source of raw materials. At the same time, the magnetic composite adsorbent prepared by the method has a high adsorption capacity and is an efficient and stable adsorbent. When it is used to treat wastewater, it can quickly adsorb tetracycline and malachite green in the wastewater and fix them on the surface of the adsorbent, thereby achieving efficient wastewater purification, and can be quickly recovered by magnetic force.
[0025] (4) The magnetic composite adsorbent prepared by the method for preparing the magnetic composite adsorbent for removing tetracycline and malachite green provided by the present invention has magnetism, can be recovered and reused multiple times by applying an external magnetic field, is environmentally friendly and energy-saving, and has high product added value.
[0026] (5) The magnetic composite adsorbent prepared by the preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green provided by the present invention can be widely used in the treatment of colored dye wastewater and antibiotics in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 The XRD diagram of the magnetic composite adsorbent prepared in Example 1 provided by the present invention;
[0029] Figure 2 A curve showing the change in removal rate of a 200 mg / L malachite green solution by the magnetic composite adsorbent prepared in Example 1 provided by the present invention as a function of treatment time;
[0030] Figure 3 A curve showing the change in removal rate of a 300 mg / L malachite green solution by the magnetic composite adsorbent prepared in Example 1 provided by the present invention as a function of treatment time;
[0031] Figure 4 A curve showing the change in removal rate of a 10 mg / L tetracycline solution by the magnetic composite adsorbent prepared in Example 1 provided by the present invention as a function of treatment time;
[0032] Figure 5 A curve showing the change in removal rate of a 100 mg / L malachite green solution by the magnetic composite adsorbent prepared in Example 2 provided by the present invention as a function of treatment time;
[0033] Figure 6 A curve showing the change in removal rate of a 200 mg / L malachite green solution by the magnetic composite adsorbent prepared in Example 2 provided by the present invention as a function of treatment time;
[0034] Figure 7 A curve showing the change in removal rate of a 10 mg / L tetracycline solution by the magnetic composite adsorbent prepared in Example 2 provided by the present invention as a function of treatment time;
[0035] Figure 8 A comparison chart of the removal rate of a 300 mg / L malachite green solution after four cycles of use of the magnetic composite adsorbent prepared in Example 1 of the present invention;
[0036] Fig. 9 This is a comparison chart of the removal rate of a 10 mg / L tetracycline solution after the magnetic composite adsorbent prepared in Example 1 provided by the present invention was recycled four times;
[0037] Fig.10 This is a comparison chart of the removal rate of the malachite green solution with a concentration of 200 mg / L after the magnetic composite adsorbent prepared in Example 2 provided by the present invention is recycled for four times;
[0038] Fig.11 This is a comparison chart of the removal rates of a 10 mg / L tetracycline solution using the magnetic composite adsorbent prepared in Example 2 provided by the present invention after four cycles. DETAILED DESCRIPTION
[0039] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0040] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0041] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0042] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0043] In a first aspect, the present invention provides a method for preparing a magnetic composite adsorbent for removing tetracycline and malachite green, comprising the following steps:
[0044] A magnesium source, an iron source, citric acid and water are mixed and subjected to a complex reaction, and a sol is obtained after the reaction is completed.
[0045] In the sol-gel self-propagating method, the role of citric acid includes: (1) Citric acid can make metal ions evenly dispersed in the citric acid aqueous solution. When the system begins to form a sol state, the steric hindrance of citric acid can reduce the cohesive force between the colloid particles, increase the stability of the colloid particles, and reduce the agglomeration strength, so that the sintered product has not only a small particle size but also a uniform distribution. (2) In the sol-gel self-propagating process, citric acid can also participate in the combustion reaction as a fuel, which helps the reaction and the formation of products. (3) Citric acid can form complexes with metal ions. This complex plays a role in stabilizing metal ions during the formation and combustion of gel, preventing metal ions from segregating or precipitating during the reaction. (4) Citric acid can also be used to adjust the pH value of the sol, thereby controlling the gelation process of the sol and the properties of the product; (5) The addition of citric acid can also affect the microstructure of the material, such as porosity, specific surface area, etc. These factors have a direct impact on the adsorption properties of the material.
[0046] The pH of the sol is adjusted and heated to form a gel. By adjusting the pH of the sol, the formation and stability of the sol in the sol-gel self-propagating method, the morphology and structure of the gel, and the stability of the metal ions can be controlled, thereby controlling the microstructure and performance of the material.
[0047] The gel is ignited to make it fully burn to obtain a precursor. Compared with heating the gel, the gel ignition in the present application can be carried out at room temperature, which is simple to operate and consumes less energy.
[0048] In some specific embodiments, during the process of igniting the gel, a small amount of ethanol is added to the gel to promote combustion.
[0049] The precursor is calcined and then cooled to obtain a magnetic composite adsorbent for removing tetracycline and malachite green.
[0050] Wherein, the calcination temperature is less than 450°C.
[0051] The preparation method of the present invention has a low calcination temperature, so the magnetic composite adsorbent contains not only magnesium ferrite but also ferroferric oxide. Ferroferric oxide not only has a high adsorption capacity but also has strong magnetism, so it is easy to recycle and reuse, and is a good catalytic material for wastewater treatment, which can remove dyes and water antibiotics from water.
[0052] The main components of the magnetic composite adsorbent include magnesium ferrite and ferroferric oxide. Among them, magnesium ferrite has a large specific surface area, a stable crystal structure, and a high adsorption capacity. In addition, magnesium ferrite is magnetic, and it can be quickly recovered from various wastewaters through magnetism, solving the problem that the adsorbent is difficult to separate. In addition, magnesium ferrite also has good stability and repeatability, so it can be used as an adsorbent in the environment.
[0053] The preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green provided by the present invention uses water as a solvent and controls a relatively low calcination temperature to prepare a magnetic composite adsorbent with a specific composition, the main components of which are magnesium ferrite and ferroferric oxide. The magnetic composite adsorbent has a good treatment effect on tetracycline and malachite green, a high removal rate, a fast removal rate, and a short removal time. In addition, the magnetic composite adsorbent still has a good removal effect on malachite green with a relatively high concentration.
[0054] Furthermore, the present invention prepares a magnetic composite adsorbent by a sol-gel one-pot method. On the one hand, the one-pot synthesis method is simple, easy to operate, suitable for large-scale production, and has low raw material cost, is easy to obtain, and has a wide range of raw material sources; on the other hand, spinel-type magnesium ferrite has magnetic properties. After being compounded with ferroferric oxide, it can not only increase the adsorption capacity, but also quickly recover the adsorbent by magnetic force. And spinel magnesium ferrite has a unique crystal structure and physicochemical properties, such as high specific surface area, surface active sites, and excellent magnetism, etc. These characteristics make it an efficient and stable adsorbent. When treating wastewater, the magnetic composite adsorbent can quickly adsorb dye molecules and antibiotics in the wastewater and fix them on the adsorbent surface, thereby achieving efficient wastewater purification.
[0055] In some specific embodiments, the water is deionized water.
[0056] In some specific embodiments, the preparation method specifically includes: adding a magnesium source and an iron source to a certain amount of deionized water, stirring for a period of time, and then adding citric acid thereto to carry out a complex reaction, and after reacting for a period of time, adding an alkali solution (such as ammonia water) thereto to adjust the pH value of the reaction system to obtain a sol; then heating the sol to gradually form a gel; igniting the gel to obtain a precursor; calcining the precursor, and cooling it to obtain a magnetic composite adsorbent.
[0057] In some specific embodiments, the magnesium source includes a magnesium-containing compound, such as magnesium nitrate, but is not limited thereto.
[0058] In some specific embodiments, the iron source includes an iron-containing compound, such as ferric nitrate, but is not limited thereto.
[0059] In order to further improve the degradation effect of the magnetic composite adsorbent on malachite green and tetracycline, increase the removal rate and shorten the removal time, the present invention optimizes the raw material ratio, and parameters such as temperature and time in the preparation process as follows.
[0060] In some specific embodiments, the calcination temperature is 350-445°C, including but not limited to any one of 350°C, 355°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 445°C or a range between any two of them.
[0061] In some specific embodiments, the calcination holding time is ≥1h, including but not limited to any one of 1h, 2h, 3h, 4h, 6h, 8h, 10h, 12h, 15h, 20h or a range between any two of them.
[0062] In some specific embodiments, during the mixing process, the molar ratio of the magnesium element in the magnesium source to the iron element in the iron source is 0.8 to 1.2:2, for example, 0.9:1, 1:1 or 1.1:1.
[0063] In some specific embodiments, the ratio of the molar amount of the citric acid to the sum of the molar amounts of the magnesium element in the magnesium source and the iron element in the iron source is 0.8 to 1.2:1, for example, 0.9:1, 1:1 or 1.1:1.
[0064] In some specific embodiments, the temperature of the complexation reaction is 40-90°C, including but not limited to any point value of 50°C, 60°C, 70°C, 80°C or a range between any two of them.
[0065] In some specific embodiments, the complexation reaction time is ≥10 min, including but not limited to any one of 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 120 min, 180 min, 240 min, 300 min or a range between any two of them.
[0066] In some specific embodiments, the pH of the sol is adjusted to 7-11, including but not limited to any one of 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11 or a range between any two of them.
[0067] In a second aspect, the present invention provides a magnetic composite adsorbent obtained by the preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green, wherein the magnetic composite adsorbent is composed of magnesium ferrite and ferrosoferric oxide.
[0068] The magnetic composite adsorbent provided by the invention has good treatment effects on malachite green and tetracycline, has a high removal rate, a short removal time, and can be recycled and reused after use.
[0069] In a third aspect, the present invention also provides the use of the magnetic composite adsorbent in the adsorption and removal of tetracycline and malachite green.
[0070] The magnetic composite adsorbent provided by the invention has good removal effects on malachite green and tetracycline and can be widely used.
[0071] In some specific embodiments, the removal rate of the magnetic composite adsorbent for a tetracycline solution with a concentration of ≤10 mg / L is ≥65%, including but not limited to any point value of 70%, 75%, 80%, 85%, 90%, 95%, 98%, 100% or a range value between any two of them.
[0072] In some specific embodiments, the removal rate of the magnetic composite adsorbent for malachite green solution with a concentration of ≤100 mg / L is ≥90%, including but not limited to any point value of 91%, 92%, 93%, 94%, 95%, 96%, 98%, 99%, 100% or a range value between any two of them.
[0073] In some specific embodiments, the removal rate of the magnetic composite adsorbent for malachite green solution with a concentration of ≤200 mg / L is ≥98%, including but not limited to any point value of 99%, 100% or any range value between the two.
[0074] In some specific embodiments, the removal rate of the magnetic composite adsorbent for malachite green solution with a concentration of ≤300 mg / L is ≥98%, including but not limited to any point value of 99%, 100% or any range value between the two.
[0075] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0076] Example 1
[0077] The preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green provided in this embodiment comprises the following steps:
[0078] Add 2 mol of ferric nitrate and 1.1 mol of magnesium nitrate to a total volume of 30 mL of deionized water and stir evenly, then add 3.3 mol of citric acid to it, and carry out complexation reaction at 45°C to obtain a sol. Then adjust the pH value of the sol to 8 with an ammonia solution, and then continue to heat the sol to form a gel, then add ethanol to the gel and ignite it to make it fully burn, and after the combustion is completed, a precursor is obtained. The precursor is calcined at 400°C for 2h to obtain a magnetic composite adsorbent.
[0079] like Figure 1 The XRD pattern of the magnetic composite adsorbent prepared in this embodiment is shown in FIG. Figure 1 It can be seen that the main components of the magnetic composite adsorbent prepared in this embodiment are magnesium ferrite (MgFe2O4) and ferrosoferric oxide.
[0080] Example 2
[0081] The preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green provided in this embodiment is basically the same as that in Example 1, except that the molar amount of citric acid is replaced with 3.1 mol.
[0082] Example 3
[0083] The preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green provided in this embodiment is basically the same as that in Example 1, except that the calcination temperature of the precursor is replaced with 350° C., and the calcination time is replaced with 2.5 h.
[0084] Example 4
[0085] The preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green provided in this embodiment is basically the same as that in Example 1, except that the system temperature of the complexation reaction is replaced with 65°C.
[0086] Example 5
[0087] The preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green provided in this embodiment is basically the same as that in Example 1, except that the pH value of the sol is adjusted to 9 with an ammonia solution.
[0088] Example 6
[0089] The preparation method of the magnetic composite adsorbent for removing tetracycline and malachite green provided in this embodiment is basically the same as that in Example 1, except that the molar amount of magnesium nitrate is replaced with 0.8 mol.
[0090] Comparative Example 1
[0091] The preparation method of the adsorbent provided in this comparative example is basically the same as that in Example 1, except that the molar amount of ferric nitrate is replaced by 1 mol, and the molar amount of magnesium nitrate is replaced by 1 mol. That is, in this comparative example, the molar ratio of the magnesium element in the magnesium source to the iron element in the iron source is 2:2, and the ratio of the molar amount of citric acid to the sum of the molar amounts of the magnesium element in the magnesium source and the iron element in the iron source is 1.65:1.
[0092] Comparative Example 2
[0093] The adsorbent provided in this comparative example is magnesium ferrite.
[0094] Comparative Example 3
[0095] The adsorbent provided in this comparative example is ferrosoferric oxide.
[0096] Comparative Example 4
[0097] The preparation method of the adsorbent provided in this comparative example is substantially the same as that of Example 1, except that citric acid is not added.
[0098] Comparative Example 5
[0099] The preparation method of the adsorbent provided in this comparative example is basically the same as that of Example 1, except that, instead of using an aqueous ammonia solution, a dilute hydrochloric acid solution is used to adjust the pH value of the sol to 2.
[0100] Comparative Example 6
[0101] The preparation method of the adsorbent provided in this comparative example is basically the same as that of Example 1, except that, instead of using an aqueous ammonia solution, a dilute hydrochloric acid solution is used to adjust the pH value of the sol to 4.
[0102] Comparative Example 7
[0103] The preparation method of the adsorbent provided in this comparative example is basically the same as that of Example 1, except that, instead of using an aqueous ammonia solution, a dilute hydrochloric acid solution is used to adjust the pH value of the sol to 6.
[0104] Experimental example
[0105] The magnetic composite adsorbents prepared in the above embodiments and the adsorbents prepared in the comparative examples were respectively used to carry out malachite green and tetracycline degradation tests. After the malachite green and tetracycline degradation tests were completed, the magnetic composite adsorbents were recovered, and the removal rate and recovery rate of malachite green and tetracycline by each group of adsorbents were calculated. The results are shown in Table 1.
[0106] Among them, the test method of malachite green degradation test is as follows: transfer 100ml of malachite green solution of a certain concentration, measure the initial concentration of the malachite green solution, add the weighed adsorbent (50mg) into the malachite green solution, oscillate under natural light, and start timing; take malachite green solution (6ml) every 20 to 30 minutes, measure the concentration of the supernatant after centrifugation and magnetic separation, and examine its change pattern with time; when the removal equilibrium is reached, calculate the removal rate of the malachite green solution by each adsorbent, separate the magnetic composite adsorbent with a magnet, and then use anhydrous ethanol and distilled water to alternately wash and regenerate the magnetic composite adsorbent, and calculate the recovery rate of the magnetic composite adsorbent.
[0107] The test method of tetracycline degradation test is as follows: take 100ml of tetracycline solution of a certain concentration, measure the initial concentration of the tetracycline solution, add the weighed adsorbent (10mg) into the tetracycline solution, oscillate under natural light, and start timing; take tetracycline solution (6ml) every 20 to 30 minutes, measure the concentration of the supernatant after centrifugation and magnetic separation, and observe its change pattern with time; when the removal equilibrium is reached, calculate the removal rate of the tetracycline solution by each adsorbent, separate the magnetic composite adsorbent with a magnet, and then wash and regenerate the magnetic composite adsorbent with anhydrous ethanol and distilled water alternately, and calculate the recovery rate of the magnetic composite adsorbent.
[0108] Table 1 Removal rate of malachite green solution by various magnetic composite adsorbents
[0109]
[0110] Table 2 Removal rate of tetracycline solution by various magnetic composite adsorbents
[0111]
[0112]
[0113] The removal rate of the magnetic composite adsorbent prepared in Example 1 for 200 mg / L malachite green solution as a function of treatment time is shown in FIG. Figure 2 The removal rate of the magnetic composite adsorbent prepared in Example 1 for 300 mg / L malachite green solution varies with the treatment time. Figure 3 The removal rate of the magnetic composite adsorbent prepared in Example 1 for 10 mg / L tetracycline solution changes with the treatment time as shown in Figure 4 The removal rate of the magnetic composite adsorbent prepared in Example 2 for 100 mg / L malachite green solution varies with the treatment time. Figure 5 The removal rate of the magnetic composite adsorbent prepared in Example 2 for 200 mg / L malachite green solution varies with the treatment time. Figure 6 The removal rate of the magnetic composite adsorbent prepared in Example 2 for 10 mg / L tetracycline solution changes with the treatment time as shown in Figure 7 shown.
[0114] It can be seen from Table 1 that the magnetic composite adsorbent prepared in each embodiment has a high removal rate for each high concentration malachite green solution, and the removal time is short; while the adsorbent prepared in each comparative example has a low removal rate for the malachite green solution, and the removal time is long.
[0115] It can be seen from Table 2 that the magnetic composite adsorbents prepared in the embodiments have a high removal rate for the tetracycline solution with a concentration of 10 mg / L, and the removal time is short; while the adsorbents prepared in the comparative examples have a low removal rate for the tetracycline solution, and the removal time is long.
[0116] In addition, the magnetic composite adsorbents prepared in each embodiment have a high recovery rate and can be reused. Specifically, the magnetic composite adsorbents recovered in Embodiment 1 and Embodiment 2 were used to continue the adsorption and degradation test of malachite green and tetracycline, and the recovery was repeated four times. Among them, the comparison chart of the removal rate of 300 mg / L malachite green by the magnetic composite adsorbent prepared in Embodiment 1 after four times of repeated recovery is shown in FIG. Figure 8 As shown, the removal rate comparison of 10 mg / L tetracycline by the magnetic composite adsorbent prepared in Example 1 after four repeated recycling is shown in FIG. Fig. 9 As shown, the magnetic composite adsorbent prepared in Example 2 was recycled four times for a comparison of the removal rate of 200 mg / L malachite green. Fig.10 As shown, the magnetic composite adsorbent prepared in Example 2 was recycled four times for a comparison of the removal rate of 10 mg / L tetracycline. Fig.11 As shown. Figure 8 and Fig.10 It can be seen that after the fourth recovery, the magnetic composite adsorbent still has a high removal rate for high concentration malachite green solution. Fig. 9 and Fig.11 It can be seen that after the fourth recovery, the magnetic composite adsorbent still has a high removal rate for 10 mg / L tetracycline solution.
[0117] In summary, the magnetic composite adsorbent prepared by the method provided by the present invention has a significant effect on the degradation of malachite green. The initial concentration of the malachite green solution is high, the removal rate is high, and the magnetic separation and recovery effect of the magnetic composite adsorbent is very good. Figure 8 and Fig.10 , within 140 minutes, the removal rate of the first adsorption degradation experiment of Example 1 was 100%, the first removal rate of recycling was 99.21%, the second removal rate of recycling was 97.36%, the third removal rate of recycling was 94.58%, and the fourth removal rate of recycling was 91.62%; within 240 minutes, the removal rate of the first adsorption degradation experiment of Example 2 was 99%, the first removal rate of recycling was 97.85%, the second removal rate of recycling was 94.77%, the third removal rate of recycling was 92.46%, and the fourth removal rate of recycling was 90.09%. It can be seen that when the magnetic composite adsorbent prepared by the present invention is repeatedly used, the removal rate of the malachite green solution remains basically unchanged.
[0118] At the same time, the magnetic composite adsorbent prepared by the method provided by the present invention has a significant degradation effect on the antibiotic tetracycline. The removal rate of the tetracycline solution is high, and the magnetic separation and recovery effect of the magnetic composite adsorbent is very good. Fig. 9 and Fig.11 , within 200 minutes, the removal rate of the first adsorption degradation experiment of Example 1 was 93%, the first removal rate of recycling was 90.84%, the second removal rate of recycling was 88.61%, the third removal rate of recycling was 85.43%, and the fourth removal rate of recycling was 81.57%; within 200 minutes, the removal rate of the first adsorption degradation experiment of Example 2 was 86%, the first removal rate of recycling was 84.71%, the second removal rate of recycling was 81.75%, the third removal rate of recycling was 80.03%, and the fourth removal rate of recycling was 77.95%. It can be seen that when the magnetic composite adsorbent prepared by the present invention is repeatedly used, the removal rate of the tetracycline solution remains basically unchanged.
[0119] In addition, the preparation method of the magnetic composite adsorbent provided by the present invention is simple to operate, low in cost, and energy-saving, and can be widely used in the degradation treatment of dyes and antibiotics.
[0120] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a magnetic composite adsorbent for removing tetracycline and malachite green, characterized in that: The steps include: A magnesium source, an iron source, citric acid and water are mixed and subjected to a complex reaction to obtain a sol; Adjusting the pH of the sol and heating it to form a gel; igniting the gel to obtain a precursor; The precursor is calcined to obtain the magnetic composite adsorbent; Wherein, the calcination temperature is less than 450°C; The main components of the magnetic composite adsorbent include magnesium ferrite and ferroferric oxide.
2. The method for preparing the magnetic composite adsorbent for removing tetracycline and malachite green according to claim 1, characterized in that: The calcination temperature is 350-445°C.
3. The method for preparing the magnetic composite adsorbent for removing tetracycline and malachite green according to claim 1, characterized in that: During the mixing process, the molar ratio of the magnesium element in the magnesium source to the iron element in the iron source is 0.8-1.2:
2.
4. The method for preparing the magnetic composite adsorbent for removing tetracycline and malachite green according to claim 1, characterized in that: The ratio of the molar amount of the citric acid to the sum of the molar amounts of the magnesium element in the magnesium source and the iron element in the iron source is 0.8 to 1.2:
1.
5. The method for preparing the magnetic composite adsorbent for removing tetracycline and malachite green according to claim 1, characterized in that: The temperature of the complexation reaction is 40-90°C.
6. The method for preparing the magnetic composite adsorbent for removing tetracycline and malachite green according to claim 1, characterized in that: The pH of the sol is adjusted to 7-11.
7. The magnetic composite adsorbent obtained by the method for preparing a magnetic composite adsorbent for removing tetracycline and malachite green according to any one of claims 1 to 6, characterized in that: The magnetic composite adsorbent consists of magnesium ferrite and ferroferric oxide.
8. Use of the magnetic composite adsorbent as claimed in claim 7 in the adsorption and removal of tetracycline and malachite green.
9. The use of the magnetic composite adsorbent according to claim 8 in the adsorption and removal of tetracycline and malachite green, characterized in that: The removal rate of the magnetic composite adsorbent for a tetracycline solution with a concentration of ≤10 mg / L is ≥65%.
10. The use of the magnetic composite adsorbent according to claim 8 in the adsorption and removal of tetracycline and malachite green, characterized in that: The removal rate of the magnetic composite adsorbent for the malachite green solution with a concentration of ≤100 mg / L is ≥90%.